Analisis Teknik Komunikasi Persuasif Dakwah Dalam Mengurangi Judi Online (Studi Pada Masyarakat Desa Tanjung Raman Kecamatan Pendopo) - Windu Santana; Sumaina Duku; Sri Hertimi (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study aims to analyze persuasive communication techniques in da'wah to reduce online gambling practices among the community of Tanjung Raman Village, Pendopo District. The increasing phenomenon of online gambling has become a serious concern due to its impact on social, economic, and moral aspects. This research uses a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation involving religious leaders, community members, and individuals who had been involved in online gambling activities. The results show that persuasive communication techniques in da'wah include emotional, rational, and religious approaches. The emotional approach is carried out by appealing to the feelings and personal experiences of the community, the rational approach by providing understanding of the negative impacts of online gambling, and the religious approach by emphasizing religious values and moral consequences. In addition, the use of da'wah media such as sermons, religious gatherings, and interpersonal communication has proven effective in influencing behavioral change in the community. The study concludes that persuasive communication in da'wah plays an important role in reducing online gambling practices, especially when delivered contextually, consistently, and involving credible community figures.